Assessment of a Membrane Filter Coated with Hygroscopic Glycerol for Improved Recovery of Airborne Viable Bacteriophage MS2 - Mohammad Washeem; William B. Vass; Drew W. Becker; Amin Shirkhani; Sripriya Nannu Shankar; Yuetong Zhang; Morteza Alipanah; Z. Hugh Fan; John A. Lednicky; Chang-Yu Wu (Aerosol and Air Quality Research)
Abstract The viability of viruses collected on membrane filters during air sampling is compromised by desiccation. This leads to an underestimation of the concentration of viable viruses in the air. We investigated whether adding a hygroscopic glycerol coating to membrane filters could enhance the recovery of viable bacteriophage MS2 collected through air sampling. Mixed cellulose ester (MCE) filters were coated with glycerol and compared with as-packaged filters (APF) as a control to determine the impact of glycerol on MS2 viability. First, MS2 viability upon direct deposition of MS2 suspension on APF vs. glycerol-coated filters (GCF) was assessed at benchtop. On average 121% more viable MS2 were recovered from GCF than APF (p = 0.031). MS2 was then aerosolized and collected onto APF, GCF, phosphate-buffered saline (PBS)-wetted filters (PWF), and gelatin filters (GF). All filter types collected statistically similar (p > 0.05) amounts of aerosolized virus at 50% RH according to RT-qPCR analysis. Viable virus recovery from GCF was significantly lower than from APF (p = 0.011) at 50% RH but significantly higher (p = 0.0004) at 80% RH. APF and GCF preconditioned for 30 minutes at 80% RH were also assessed for MS2 aerosol sampling. Results showed higher viable virus recovery from GCF than either APF (p = 0.021) or GF (p = 0.006). High RH in aerosols facilitated viability conservation of MS2 on GCF, leading to improved recovery of viable virus from membrane filters.